ANALISIS PENGOLAHAN SAMPAH REDUCE, REUSE, DAN RECYCLE (3R) PADA MASYARAKAT DI KOTA PAYAKUMBUH - Ediana, Dina; Fatma, Fitria; Yuniliza, Yuniliza (Jurnal Endurance, 2018)
The problem of urban garbage has become a problem of the City Government. Based on the Periodic Report of 2014, the volume of garbage transported in Payakumbuh is 193-206 m3 per day or 5,750-5,833 m3 per month, and increased by 235-261 m3 per day or 6,210-6840 m3 per month in 2015. Payakumbuh Government issued Local Regulation Number 4 Year 2014 on garbage management, referring to the Law of the Republic of Indonesia number 18 of 2008. Regional Regulation contains about garbage management by using 3 R method (Reduce, Reuse, Recycle). Implementation of 3 R method involving community participation as garbage producer. The purposeof this research was to analyze community behavior of garbage processing 3R in Payakumbuh. Quantitative method was used in this research, is descriptive analytics with cross sectional design. Results and discussion, univariate analysis known to the respondents who work as much as 54 (56.2%), high knowledge of respondents more 71 (73%), more positive respondents 52 (54.17%), respondents who do processing garbage 3R higher 52 (54,17%). The result of bivariate analysis is known that there is relationship of attitude (p = 0,028) to 3R garbage processing. There is no relationship of job status (p = 0,122), knowledge (p = 0,36) to 3R garbage treatment. The existence of attitude relation on 3R garbage processing. It is hoped empowerment program will be improved, so that the community will be participate on 3 R garbage processing. (Reduse, Reuse, Recycle). Masalah persampahan perkotaan sudah menjadi masalah Pemerintah Kota. Berdasarkan Laporan Periodik perbulan tahun 2014, volume sampah diangkut di Kota Payakumbuh sebesar 193-206 m3 perhari atau 5.750-5.833 m3 perbulan, dan meningkat sebesar 235-261 m3 perhari atau 6.210-6840 m3 perbulan pada tahun 2015. Pemerintah Payakumbuh menerbitkan Peraturan Daerah Nomor 4 Tahun 2014 tentang  pengelolaan sampah, mengacu  pada Undang-Undang Republik Indonesia nomor 18 Tahun 2008. Peraturan Daerah berisi tentang  pengelolaan sampah  masyarakat dengan menggunakan  metode 3 R (Reduce, Reuse, Recycle). Penerapan metode 3 R yang melibatkan peran serta masyarakat sebagai produsen sampah. Tujuan untuk menganalisis perilaku pengolahan sampah 3R Masyarakat di Kota Payakumbuh.Metode penelitian ini menggunakan metode penelitian kuantitatif, bersifat deskriptif analitik dengan desain cross sectional. Hasil dan pembahasan, analisis univariat diketahui responden yang bekerja sebanyak 54  (56,2 %), tingkat pengetahuan responden yang tinggi lebih banyak 71 (73%), sikap responden yang positif lebih banyak 52 (54,17%), responden yang melakukan pengolahan sampah 3R lebih  tinggi 52 (54,17%). Hasil analisis bivariat diketahui ada hubungan sikap (p=0,028) terhadap pegolahan sampah 3R. Tidak ada hubungan status pekerjaan (p=0,122), pengetahuan (p=0,36) terhadap pengolahan sampah 3R.  Adanya hubungan sikap terhadap pengolahan sampah 3R.Diharapkan program pemberdayaan lebih ditingkatkan, agar  terbina kelompok masyarakat dalam melakukan pengolahan sampah 3 R.(Reduse, Reuse, Recycle).